Analysis and Simulation Mathematical Model of Zika Disease with One Serotype Virus Zika - Maysaroh, Ais; Waluya, St. Budi; Wuryanto, Wuryanto (Unnes Journal of Mathematics, 2019)
In Indonesia, there are five cases of patients reported Zika disease. This study discusses the mathematical models for the spread of Zika disease with one serotype Zika virus. The mathematical models used in the form SEIR models. The purpose of this study is to develop a mathematical model, analyze the point of stability, and interpret the mathematical model simulation with maple. In the construction of the model is obtained mathematical model with two points of equilibrium that is the point of disease-free equilibrium and endemic equilibrium point. The analysis carried out to produce numbers basic reproduction ratio (R0). After analyzing two equilibrium point it can be concluded that the disease-free equilibrium point will be asymptotically stable if R0<1. While the endemic equilibrium point will be asymptotically stable if R0>1. Furthermore, to illustrate the model of the simulation model using Maple program produces some of the facts, that is the smaller chance of spread Zika virus by mosquitoes to humans in an area then the smaller individual human Zika virus infected and otherwise. Then the greater value of intervention mosquito fumigation are given on the dwindling number of individuals infected human Zika virusZika Virus